8*(2p-4)*3p=20

Simple and best practice solution for 8*(2p-4)*3p=20 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8*(2p-4)*3p=20 equation:


Simplifying
8(2p + -4) * 3p = 20

Reorder the terms:
8(-4 + 2p) * 3p = 20

Reorder the terms for easier multiplication:
8 * 3p(-4 + 2p) = 20

Multiply 8 * 3
24p(-4 + 2p) = 20
(-4 * 24p + 2p * 24p) = 20
(-96p + 48p2) = 20

Solving
-96p + 48p2 = 20

Solving for variable 'p'.

Reorder the terms:
-20 + -96p + 48p2 = 20 + -20

Combine like terms: 20 + -20 = 0
-20 + -96p + 48p2 = 0

Factor out the Greatest Common Factor (GCF), '4'.
4(-5 + -24p + 12p2) = 0

Ignore the factor 4.

Subproblem 1

Set the factor '(-5 + -24p + 12p2)' equal to zero and attempt to solve: Simplifying -5 + -24p + 12p2 = 0 Solving -5 + -24p + 12p2 = 0 Begin completing the square. Divide all terms by 12 the coefficient of the squared term: Divide each side by '12'. -0.4166666667 + -2p + p2 = 0 Move the constant term to the right: Add '0.4166666667' to each side of the equation. -0.4166666667 + -2p + 0.4166666667 + p2 = 0 + 0.4166666667 Reorder the terms: -0.4166666667 + 0.4166666667 + -2p + p2 = 0 + 0.4166666667 Combine like terms: -0.4166666667 + 0.4166666667 = 0.0000000000 0.0000000000 + -2p + p2 = 0 + 0.4166666667 -2p + p2 = 0 + 0.4166666667 Combine like terms: 0 + 0.4166666667 = 0.4166666667 -2p + p2 = 0.4166666667 The p term is -2p. Take half its coefficient (-1). Square it (1) and add it to both sides. Add '1' to each side of the equation. -2p + 1 + p2 = 0.4166666667 + 1 Reorder the terms: 1 + -2p + p2 = 0.4166666667 + 1 Combine like terms: 0.4166666667 + 1 = 1.4166666667 1 + -2p + p2 = 1.4166666667 Factor a perfect square on the left side: (p + -1)(p + -1) = 1.4166666667 Calculate the square root of the right side: 1.190238071 Break this problem into two subproblems by setting (p + -1) equal to 1.190238071 and -1.190238071.

Subproblem 1

p + -1 = 1.190238071 Simplifying p + -1 = 1.190238071 Reorder the terms: -1 + p = 1.190238071 Solving -1 + p = 1.190238071 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + p = 1.190238071 + 1 Combine like terms: -1 + 1 = 0 0 + p = 1.190238071 + 1 p = 1.190238071 + 1 Combine like terms: 1.190238071 + 1 = 2.190238071 p = 2.190238071 Simplifying p = 2.190238071

Subproblem 2

p + -1 = -1.190238071 Simplifying p + -1 = -1.190238071 Reorder the terms: -1 + p = -1.190238071 Solving -1 + p = -1.190238071 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + p = -1.190238071 + 1 Combine like terms: -1 + 1 = 0 0 + p = -1.190238071 + 1 p = -1.190238071 + 1 Combine like terms: -1.190238071 + 1 = -0.190238071 p = -0.190238071 Simplifying p = -0.190238071

Solution

The solution to the problem is based on the solutions from the subproblems. p = {2.190238071, -0.190238071}

Solution

p = {2.190238071, -0.190238071}

See similar equations:

| 6x+1+5x=-65 | | a+10=b+2 | | 1+2x=x-2-4x | | -2x-5y=-27 | | 14(d+30)=-196 | | -4+4x-5x=-14 | | 3f=(2f+8) | | 6X-12+4X-1=-X+12-3X+5 | | x+(x+10)+2x=98 | | 4x+3=x+x+29 | | 2t-1=2t-5 | | 4y+3=y+21 | | 4y+3=y+22 | | 625-25x=0 | | (35x+67y)+(-20x+41y)= | | f(x-1)=x^2+3 | | f(x-1)=x^2-3 | | 14d+30=196 | | 14z=3(4z+3) | | 10x^3-11x^2-6x=0 | | 2x-1+3=4 | | 32=-0.8m | | -3.2x=14.4 | | -1.25+.25x=0 | | -1.25+25x=0 | | x+(-26)=52 | | 3x^4+12x^2=12x^3 | | -x^2+32=(X+4)(X-4) | | 2x+2=10-8x | | 314=n+576 | | y=-5x^2+23x | | 4y-12= |

Equations solver categories